Analysis of Total Knee Arthroplasty revision causes - Postler, Anne; Lützner, Cornelia; Beyer, Franziska; Tille, Eric; Lützner, Jörg (BMC musculoskeletal disorders, 2018)
Background The number of revision Total Knee Arthroplasty (TKA) is rising in many countries. The aim of this study was the prospective assessment of the underlying causes leading to revision TKA in a tertiary care hospital and the comparison of those reasons with previously published data. Methods In this study patients who had revision TKA between 2010 and 2015 were prospectively included. Revision causes were categorized using all available information from patients’ records including preoperative diagnostics, intraoperative findings as well as the results of the periprosthetic tissue analysis. According to previous studies patients were divided into early (up to 2 years) and late revision (more than 2 years). Additional also re-revisions after already performed revision TKA were included. Results We assessed 312 patients who underwent 402 revision TKA, 89.6% of them were referred to our center for revision surgery. In 289 patients (71.9%) this was the first revision surgery after primary TKA. Among the first revisions the majority was late revisions (73.7%). One hundred thirteen patients (28.1%) had already had one or more revision surgeries before. Overall, the most frequent reason for revision was infection (36.1%) followed by aseptic loosening (21.9%) and periprosthetic fracture (13.7%). Conclusions In a specialized arthroplasty center periprosthetic joint infection (PJI) was the most common reason for revision and re-revision TKA. This is in contrast to population-based registry data and has consequences on costs as well as on success rates in such centers.